Negative plate of sodium ion battery

Through the combination of wet grinding and inorganic salt interface constructor, a nano-anode material layer is formed, which solves the structural instability caused by volume expansion of the negative electrode material of sodium ion battery during charging and discharging, and significantly improves the stability and electrical properties of the material. Chemical properties.

CN119181762APending Publication Date: 2024-12-24SHENZHEN JANAENERGY TECH CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411374598.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The structure of the negative electrode material of sodium ion battery is unstable due to volume expansion during the charging and discharging cycle, which affects the cycling performance of the battery. The theoretical capacity of existing hard carbon materials is low and prone to shattering.

Method used

The wet grinding process is used to combine the inorganic salt interface constructor and conductive carbon to form a nano-uniform negative electrode material layer. The interface construct layer is formed by adsorption of binder and anion ions, reducing material expansion stress and improving mechanical stability.

Benefits of technology

The nano-uniformity of the negative electrode material of sodium ion battery has high nano-uniformity, good structural stability and excellent electrochemical performance, and the circulation stability of the material and the energy density of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181762A_ABST
    Figure CN119181762A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium ion battery negative electrode plate, which comprises a negative electrode current collector and a negative electrode material layer coated on the negative electrode current collector negative side and / or positive side, and the negative electrode material layer comprises the following raw material components by mass: 10 parts of an aqueous binder, 70-80 parts of negative electrode material powder, 0.7-4 parts of an inorganic salt interface construction agent, and 10-20 parts of a conductive agent. The sodium ion battery negative plate has the characteristics of high nanocrystallization uniformity, good structural stability and excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a negative electrode sheet of a sodium ion battery. Background Art

[0002] In recent years, due to the shortage of lithium resources and the increase in the cost of lithium batteries, people have turned their attention to sodium-ion batteries, which have similar working principles to lithium-ion batteries. However, because sodium ions have a larger ionic radius than lithium ions, graphite, the negative electrode material for commercial lithium-ion batteries, is difficult to use directly in sodium-ion batteries. There are kinetic and thermodynamic problems with the embedding of sodium ions in graphite. With more and more in-depth research, the positive electrode materials of sodium-ion batteries have become relatively mature, but for negative electrode materials, the most mature hard carbon still has some shortcomings, such as low theoretical capacity and low compaction density, which leads to a decrease in the mass specific capacity of the battery, and a low charge and discharge platform that is easy to precipitate sodium.

[0003] Therefore, scholars have turned their attention to other negative electrode materials with higher theoretical specific capacities. These advanced negative electrode materials can achieve the coordinated embedding and reversible deintercalation of multiple sodium ions. However, the embedding of sodium ions will cause a significant expansion of the material volume, and in the subsequent charge and discharge cycle, this volume expansion may cause the material to break and pulverize, thereby affecting its cycle stability. Interface construction can suppress this problem, effectively reduce the expansion stress of the material interface, and reduce the volume expansion rate, thereby significantly improving the structural stability of the material. Summary of the invention

[0004] The object of the present invention is to provide a sodium ion battery negative electrode sheet having the characteristics of high nano-uniformity, good structural stability and excellent electrochemical performance.

[0005] The present invention can be implemented by the following technical solutions: The invention discloses a negative electrode sheet for a sodium ion battery, comprising a negative electrode current collector and a negative electrode material layer coated on the negative surface and / or positive surface of the negative electrode current collector, wherein the negative electrode material layer comprises the following raw material components by mass: 10 parts of an aqueous binder, 70-80 parts of a negative electrode material powder, 0.7-4 parts of an inorganic salt interface constructor, and 10-20 parts of a conductive agent; the proportion of the conductive carbon and the binder ensures the conductivity and mechanical stability of the electrode sheet, and the proportion of the inorganic salt is based on the following considerations: when the content of the inorganic salt is too little, it is insufficient to form a complete interface construction layer, resulting in poor structural stability of the material, and easy to break and pulverize during circulation; and when the content is too high, the interface construction layer will be too thick, affecting the mass transfer of sodium ions, and the polarization of the material will be large, so the capacity is not high. The raw material components in the negative electrode material layer are dispersed in a wet grinding solvent system and wet-grinded and mixed uniformly under a protective atmosphere.

[0006] Furthermore, the ratio of the raw material components to the wet grinding solvent is 1:1~1:20. When the wet grinding solvent is too little, the binder will dissolve and the whole will become thicker, which is not conducive to the uniform dispersion of the material and the wet grinding effect, and thus the nano-crystallization effect is not good; when the wet grinding solvent is too much, the collision between the powders will be reduced, affecting the particle size distribution of the material after ball milling, and obtaining a material with uneven size.

[0007] Furthermore, the inorganic salt interface construction agent is one or more of NaF, NaCl, Na2SO4, NaNO3, and Na2CO3, and particularly preferably inorganic salts NaF and NaCl with a relatively high Young's modulus. In the process of wet grinding, the inorganic salt will dissolve in water to become anions and cations. At the same time, high-energy ball milling can increase the activity of the negative electrode powder, destroy the structure of the negative electrode material through mechanical force, and produce corresponding defect positions. While producing defects, anions and cations are uniformly adsorbed on the surface of the negative electrode material due to the attraction between positive and negative charges. After the water is subsequently dried, the hydration disappears, and the precipitated salt realizes an interface construction layer on the surface of the negative electrode material. The realization of the interface construction layer depends on the bonding effect of the binder and the adsorption effect of anions and cations.

[0008] Furthermore, during the wet grinding process, the process control conditions are as follows: in a protective atmosphere, cyclic ball milling is performed in an intermittent manner, the ball milling time for each cycle is 30-90 minutes, the interval time is 60-90 minutes, and the number of ball milling cycles is 4-24; the ball milling frequency is in the range of 40-50Hz, so that the particle size after ball milling reaches between 200-1000nm. The intermittent ball milling method can more easily control the temperature inside the mill, because the mill can be cooled during the rest stage to avoid thermal degradation or thermal damage of the material at high temperature. In addition, different ball milling times and rest times are to adapt to different materials and grinding requirements. For materials with lower hardness, a shorter single ball milling time can prevent the material from agglomerating.

[0009] Furthermore, the elements of the negative electrode powder are composed of one or more of the sodium-intercalating active elements silicon, lead, tin, antimony, germanium, bismuth, phosphorus, and sulfur, or a combination of one or more of the non-sodium-intercalating active elements zinc, iron, cobalt, nickel, copper, and aluminum and one or more of the above-mentioned sodium-intercalating active elements.

[0010] Furthermore, the aqueous binder is one or more of carboxymethyl cellulose (CMC), polyacrylic acid (PAA), sodium alginate (SA), sodium carboxymethyl cellulose (CMC-Na), and polyacrylic acid (PAA-Na).

[0011] Furthermore, the conductive agent is one or more of carbon black, conductive graphite, carbon fiber (VGCF), carbon nanotube (CNT), graphene, Ketjen black (KB), and acetylene black (AB).

[0012] Furthermore, the wet grinding method is one or more of ball milling, sand milling, homogenizer mixing, deaerator homogenization, or mechanical stirring.

[0013] Furthermore, the protective atmosphere is argon or nitrogen.

[0014] Furthermore, the wet grinding solvent system in the wet grinding process is water.

[0015] The sodium ion battery negative electrode sheet of the present invention has the following beneficial effects: First, the nano-homogenization degree is high. In the present invention, the wet grinding method can achieve uniform nano-ization. Unlike dry grinding, which is prone to grinding dead corners, wet grinding can grind the material more uniformly and fully, and the grinding efficiency is higher. Because during the grinding process, large particles will crack under the grinding and impact of the grinding medium, and the cracks will break into small particles over time, which is the so-called grinding process. If it is dry grinding, when the cracks of the particles expand during the grinding process, due to the extrusion between the grinding medium or particles, the cracks formed may be squeezed "closed", and the cracks cannot be effectively expanded, and the large particles cannot be quickly broken to form small particles. However, if it is wet grinding, the liquid grinding medium water will enter the crack gap formed, blocking the closure of the cracks, thereby effectively making the cracks expand rapidly, which will greatly improve the grinding efficiency. At the same time, during dry grinding, due to the design of the grinding tank body, dead corners are sometimes formed, and some materials in the dead corners cannot be ground; and the present invention directly adds conductive carbon to obtain a slurry that can be directly coated, which perfectly avoids the high energy consumption problem caused by the need to dry water in wet grinding. The binder added at the same time acts as a dispersant, inhibiting the agglomeration of the material during the grinding process. After drying, the organic network formed by the binder can fix the negative electrode material and its interface construction layer after the interface construction to prevent structural changes.

[0016] Second, the structural stability is good. The inorganic salt interface construction agent is added to the present invention to obtain a thin and rigid inorganic salt interface construction layer. The inorganic salt will first dissolve in water to become anions and cations during the wet grinding process. At the same time, high-energy grinding can increase the activity of the negative electrode powder, destroy the structure of the negative electrode material through mechanical force, and produce corresponding defect positions. While the defects are generated, the anions and cations are uniformly adsorbed on the surface of the negative electrode material due to the attraction between the positive and negative charges. After the water is dried, the hydration disappears, and the precipitated salt realizes the interface construction layer on the surface of the negative electrode material. The realization of the interface construction layer depends on the bonding effect of the binder and the adsorption effect of anions and cations. The existence of the interface construction layer can inhibit the volume expansion of the material to a certain extent, and further effectively prevent the agglomeration of the material. The entire grinding process is carried out under a protective atmosphere, and the ground negative electrode material does not select a particularly active raw material, so the powder does not react easily. And because it is in a liquid environment and intermittent grinding work, a very high temperature will not be generated during the grinding process, further avoiding the oxidation of the material or other chemical reactions. At the same time, the concentration of salt added is very low, which is almost equivalent to wet grinding of negative electrode materials in water. In summary, the possibility of other side reactions occurring during the whole process and thus affecting the nano-sizing of materials and the formation of interface construction layers is very small.

[0017] Third, the electrochemical performance is excellent, and the added interface construction inorganic salt is very small, which will not reduce the energy density of the battery. The interface construction layer also prevents the agglomeration of materials and inhibits the volume deformation of materials. When the inorganic salt content is too little, it is not enough to form a complete interface construction layer, and when its content is too high, it will cause the interface construction layer to be too thick, affecting the mass transfer of sodium ions. The choice of inorganic salts tends to have a high Young's modulus, so that the interface construction layer formed has greater rigidity and can alleviate the breakage of the negative electrode material when the volume expands. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The charge and discharge curves of Example 1 and Comparative Example 1 at 100 mA / g are shown; Figure 2 The cycle performance of Example 2 and Comparative Example 2 at 660 mA / g; Figure 3 The charge and discharge curves of Example 3 and Comparative Example 3 at 100 mA / g are shown; Figure 4 The cycle performance of Example 4 and Comparative Example 4 at 660 mA / g; Figure 5 The charge and discharge curves of Example 5 and Comparative Example 5 at 100 mA / g are shown. DETAILED DESCRIPTION

[0019] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below in conjunction with embodiments.

[0020] The invention discloses a sodium ion battery negative electrode sheet, comprising a negative electrode current collector and a negative electrode material layer coated on the negative surface and / or positive surface of the negative electrode current collector, wherein the negative electrode material layer comprises the following raw material components in parts by weight: 10 parts of a water-based binder, 70-80 parts of a negative electrode material powder, 0.7-4 parts of an inorganic salt interface constructor, and 10-20 parts of a conductive agent; the raw material components in the negative electrode material layer are dispersed in a wet grinding solvent system and are wet-ground and mixed uniformly under a protective atmosphere.

[0021] Furthermore, the ratio of the raw material components to the wet grinding solvent is 1:1~1:20.

[0022] Furthermore, the inorganic salt interface constructor is one or more of NaF, NaCl, Na2SO4, NaNO3, and Na2CO3.

[0023] Furthermore, during the wet grinding process, the process control conditions are as follows: under a protective atmosphere, cyclic ball milling is carried out in an intermittent manner, the ball milling time for each cycle is 30-90 minutes, the interval time is 60-90 minutes, and the number of ball milling cycles is 4-24 times; the ball milling frequency is in the range of 40-50 Hz, so that the particle size after ball milling reaches between 200-1000 nm.

[0024] Furthermore, the elements of the negative electrode powder are composed of one or more of the sodium-intercalating active elements silicon, lead, tin, antimony, germanium, bismuth, phosphorus, and sulfur, or a combination of one or more of the non-sodium-intercalating active elements zinc, iron, cobalt, nickel, copper, and aluminum and one or more of the above-mentioned sodium-intercalating active elements.

[0025] Furthermore, the aqueous binder is one or more of carboxymethyl cellulose (CMC), polyacrylic acid (PAA), sodium alginate (SA), sodium carboxymethyl cellulose (CMC-Na), and polyacrylic acid (PAA-Na).

[0026] Furthermore, the conductive agent is one or more of carbon black, conductive graphite, carbon fiber (VGCF), carbon nanotube (CNT), graphene, Ketjen black (KB), and acetylene black (AB).

[0027] Furthermore, the wet grinding method is one or more of ball milling, sand milling, homogenizer mixing, deaerator homogenization, or mechanical stirring.

[0028] Furthermore, the protective atmosphere is argon or nitrogen.

[0029] Furthermore, the wet grinding solvent system in the wet grinding process is water.

[0030] The present invention regulates the morphology of the negative electrode material while nano-izing it, thereby improving the electrochemical performance of the material. A binder and an inorganic salt interface constructor are added during wet grinding, and wet grinding can nano-ize the negative electrode powder. In addition, during the ball milling process, multiple defect positions can be formed when the negative electrode material and the ball milling medium are ground and cut, which easily adsorbs the anions and cations of the inorganic salt, resulting in bonding, resulting in the enrichment of the anions and cations of the inorganic salt on the surface of the negative electrode. In addition, the bonding effect of the binder prevents the interface construction layer of the inorganic salt interface constructor from being destroyed during the grinding process. After adding conductive carbon, it can be directly slurried and coated. After the film is coated and dried, an interface construction layer with a special morphological structure of rigid inorganic salts will be formed on the surface of the negative electrode. The interface construction layer can inhibit the volume expansion of the negative electrode material during the cycle and improve the electrochemical performance of the negative electrode material. This wet grinding process does not introduce other impurities, and the mixture obtained by wet grinding can be directly used as a slurry for sodium ion battery coating by adding conductive carbon, which is simple to operate. During the whole process, nano-sizing can reduce the expansion stress of the material and alleviate the breakage and pulverization of the material due to volume expansion. In addition, the existence of the interface construction layer can reduce the surface energy of the nanomaterial, inhibit the agglomeration of the material and inhibit the volume deformation of the material.

[0031] The invention has different effects on different materials, but overall the electrochemical performance of the materials is improved. The reasons for the different improvement effects are: (1) The Young's modulus of the added inorganic salt interface constructor is different. The salt with a higher Young's modulus is more effective in inhibiting the volume expansion of the material and preventing the material from breaking. (2) The crystal structures of different negative electrode materials are different, resulting in different atomic arrangements, which affects their deformation and fracture characteristics during ball milling. For example, materials with a face-centered cubic (FCC) structure are generally more susceptible to plastic deformation than materials with a body-centered cubic (BCC) structure. (3) Materials with higher hardness are more difficult to grind during ball milling and require more energy and time to achieve the same refinement effect. (4) The initial particle size of the material will also affect the ball milling effect. Larger particles require more energy to refine. In general, the smaller the hardness and the easier it is to deform and break the negative electrode material, the better the performance improvement effect of the salt with a larger Young's modulus of interface construction.

[0032] Example 1 The present embodiment discloses a negative electrode sheet for a sodium ion battery, comprising a negative electrode current collector and a negative electrode material layer coated on the negative surface and / or positive surface of the negative electrode current collector, wherein the negative electrode material layer comprises the following raw material components in parts by weight: 10 parts of an aqueous binder, 80 parts of a negative electrode material powder, 2 parts of an inorganic salt interface constructor, and 10 parts of a conductive agent; the raw material components in the negative electrode material layer are dispersed in a wet grinding solvent system and are wet-ground and mixed uniformly under a protective atmosphere, and the ratio of the raw material components to the wet grinding solvent is 1:20.

[0033] During the wet grinding process, the process control conditions are: in the protective atmosphere, the ball milling is carried out in an interval manner, the ball milling time for each cycle is 90 minutes, the interval time is 75 minutes, the number of ball milling cycles is 4 times; the ball milling frequency is 50Hz, so that the particle size after ball milling reaches between 200-1000nm. The protective atmosphere is argon; the wet grinding solvent system is water; the grinding method is ball milling.

[0034] In this embodiment, the inorganic salt interface constructor is NaF and NaCl. The elements of the negative electrode powder are sodium-embedded active elements silicon and lead. The aqueous binder is carboxymethyl cellulose (CMC). The conductive agent is carbon black, conductive graphite, and carbon fiber (VGCF).

[0035] Example 2 The present embodiment discloses a negative electrode sheet for a sodium ion battery, comprising a negative electrode current collector and a negative electrode material layer coated on the negative surface and / or positive surface of the negative electrode current collector, wherein the negative electrode material layer comprises the following raw material components in parts by weight: 10 parts of an aqueous binder, 75 parts of a negative electrode material powder, 0.7 parts of an inorganic salt interface constructor, and 20 parts of a conductive agent; the raw material components in the negative electrode material layer are dispersed in a wet grinding solvent system and are evenly mixed by wet grinding under a protective atmosphere, and the ratio of the raw material components to the wet grinding solvent is 1:10.

[0036] During the wet grinding process, the process control conditions are: in the protective atmosphere, the ball milling is carried out in an interval manner, the ball milling time for each cycle is 60 minutes, the interval time is 60 minutes, the number of ball milling cycles is 24 times; the ball milling frequency is 45Hz, and the particle size after ball milling reaches 200-1000nm. The protective atmosphere is nitrogen; the wet grinding solvent system is water; the grinding method is sand grinding.

[0037] In this embodiment, the inorganic salt interface constructor is Na2CO3. The elements of the negative electrode powder are sodium-embedded active elements tin and antimony. The aqueous binder is polyacrylic acid (PAA). The conductive agent is carbon nanotubes (CNT) and graphene.

[0038] Example 3 The present embodiment discloses a negative electrode sheet for a sodium ion battery, comprising a negative electrode current collector and a negative electrode material layer coated on the negative surface and / or positive surface of the negative electrode current collector, wherein the negative electrode material layer comprises the following raw material components in parts by weight: 10 parts of an aqueous binder, 70 parts of a negative electrode material powder, 4 parts of an inorganic salt interface constructor, and 15 parts of a conductive agent; the raw material components in the negative electrode material layer are dispersed in a wet grinding solvent system and are evenly mixed by wet grinding under a protective atmosphere, and the ratio of the raw material components to the wet grinding solvent is 1:1.

[0039] During the wet grinding process, the process control conditions are: in the protective atmosphere, the ball milling is carried out in an interval manner, the ball milling time for each cycle is 30 minutes, the interval time is 90 minutes, the number of ball milling cycles is 14 times; the ball milling frequency is 45Hz, and the particle size after ball milling reaches 200-1000nm. The protective atmosphere is argon; the wet grinding solvent system is water; the grinding method is homogenizer mixing.

[0040] In this embodiment, the inorganic salt interface constructor is NaF and Na2CO3. The elements of the negative electrode powder are sodium-embedded active elements silicon and sulfur. In this embodiment, the aqueous binder is sodium alginate (SA) and sodium carboxymethyl cellulose (CMC-Na). The conductive agent is graphene, Ketjen black (KB), and acetylene black (AB).

[0041] Example 4 The present embodiment discloses a negative electrode sheet for a sodium ion battery, comprising a negative electrode current collector and a negative electrode material layer coated on the negative surface and / or positive surface of the negative electrode current collector, wherein the negative electrode material layer comprises the following raw material components in parts by weight: 10 parts of an aqueous binder, 72 parts of a negative electrode material powder, 1 part of an inorganic salt interface constructor, and 12 parts of a conductive agent; the raw material components in the negative electrode material layer are dispersed in a wet grinding solvent system and are evenly mixed by wet grinding under a protective atmosphere, and the ratio of the raw material components to the wet grinding solvent is 1:12.

[0042] During the wet grinding process, the process control conditions are: in the protective atmosphere, the ball milling is carried out in an interval manner, the ball milling time for each cycle is 40 minutes, the interval time is 70 minutes, the number of ball milling cycles is 10 times; the ball milling frequency is 40Hz, and the particle size after ball milling reaches 200-1000nm. The protective atmosphere is nitrogen; the wet grinding solvent system is water; the grinding method is mechanical stirring.

[0043] In this embodiment, the inorganic salt interface constructor is NaCl and Na2SO4. The elements of the negative electrode powder are sodium-intercalating active element tin and non-sodium-intercalating active element zinc. The aqueous binder is polyacrylic acid (PAA-Na). The conductive agent is carbon black, conductive graphite, carbon fiber (VGCF) and acetylene black (AB).

[0044] Example 5 The present embodiment discloses a negative electrode sheet for a sodium ion battery, comprising a negative electrode current collector and a negative electrode material layer coated on the negative surface and / or positive surface of the negative electrode current collector, wherein the negative electrode material layer comprises the following raw material components in parts by weight: 10 parts of an aqueous binder, 78 parts of a negative electrode material powder, 3 parts of an inorganic salt interface constructor, and 15 parts of a conductive agent; the raw material components in the negative electrode material layer are dispersed in a wet grinding solvent system and are evenly mixed by wet grinding under a protective atmosphere, and the ratio of the raw material components to the wet grinding solvent is 1:8.

[0045] During the wet grinding process, the process control conditions are as follows: in the protective atmosphere, the ball milling is carried out in an interval manner, the ball milling time for each cycle is 80 minutes, the interval time is 70 minutes, the number of ball milling cycles is 17 times; the ball milling frequency is 50Hz, and the particle size after ball milling reaches between 200-1000nm. The protective atmosphere is argon; the wet grinding solvent system is water; the grinding method is ball milling.

[0046] In this embodiment, the inorganic salt interface constructor is NaF, NaCl, and Na2CO3. The elements of the negative electrode powder are sodium-intercalating active elements germanium, bismuth, and phosphorus, and non-sodium-intercalating active elements cobalt and nickel. The aqueous binder is polyacrylic acid (PAA-Na). The conductive agent is carbon black, conductive graphite, and carbon fiber (VGCF).

[0047] Example 6 The present embodiment discloses a negative electrode sheet for a sodium ion battery, comprising a negative electrode current collector and a negative electrode material layer coated on the negative surface and / or positive surface of the negative electrode current collector, wherein the negative electrode material layer comprises the following raw material components in parts by weight: 10 parts of an aqueous binder, 75 parts of a negative electrode material powder, 2 parts of an inorganic salt interface constructor, and 18 parts of a conductive agent; the raw material components in the negative electrode material layer are dispersed in a wet grinding solvent system and are evenly mixed by wet grinding under a protective atmosphere, and the ratio of the raw material components to the wet grinding solvent is 1:15.

[0048] During the wet grinding process, the process control conditions are: in the protective atmosphere, the ball milling is carried out in an interval manner, the ball milling time for each cycle is 50 minutes, the interval time is 70 minutes, the number of ball milling cycles is 20 times; the ball milling frequency is in the range of 40-50Hz, and the particle size after ball milling reaches 200-1000nm. The protective atmosphere is nitrogen; the wet grinding solvent system is water; the grinding method is ball milling and sand milling.

[0049] In this embodiment, the inorganic salt interface constructor is NaF, NaCl, Na2SO4, NaNO3, Na2CO3. The elements of the negative electrode powder are sodium-intercalating active elements antimony, germanium, bismuth, phosphorus and non-sodium-intercalating active elements cobalt and nickel. The aqueous binder is carboxymethyl cellulose (CMC), polyacrylic acid (PAA), sodium alginate (SA). The conductive agent is graphene, Ketjen black (KB), acetylene black (AB).

[0050] Application Example 1 This application example relates to a negative electrode sheet for a sodium ion battery, wherein the negative electrode is tin powder, and the preparation method thereof is as follows: Step 1, weighing 0.1 g of water-based binder carboxymethyl cellulose (CMC) and 0.8 g of negative electrode active material tin powder, and then adding 1.6 mg of sodium fluoride and 6.59 g of water as raw materials, these raw materials are sand-milled in an argon atmosphere for 60 min per cycle, with an interval time of 60 min, and the sand-milling cycle is repeated 8 times to obtain slurry A; Step 2, add 0.1 g of conductive agent SuperP to slurry A, continue mixing for 0.5 h to obtain slurry B, and directly apply slurry B to obtain a uniformly coated electrode A; Step 3, the coated electrode A obtained in step 2 is baked in a 60°C oven for 12 h to dry out the moisture, thereby obtaining a negative electrode of the battery; Application Example 2 This application example relates to a negative electrode sheet for a sodium ion battery, wherein the negative electrode is antimony powder, and the preparation method thereof is as follows: Step 1: Weigh 0.2 g of aqueous binder polyacrylic acid (PAA) and 0.14 g of negative electrode active material antimony powder, add 4.2 mg of sodium chloride and 11.8 g of water as raw materials, and ball mill these raw materials in an argon atmosphere for 60 min per cycle, with an interval time of 90 min, and sand mill for 4 times to obtain slurry A; Step 2, add 0.4 g of conductive agent AB to slurry A, continue mixing for 1 h to obtain slurry B, and directly apply slurry B to obtain a uniformly coated electrode A; Step 3, the coated electrode A obtained in step 2 is dried in a 60°C oven for 8 h to obtain a negative electrode of the battery; Application Example 3 This application example relates to a negative electrode sheet for a sodium ion battery, wherein the negative electrode is red phosphorus powder, and the preparation method thereof is as follows: Step 1: Weigh 0.1 g of aqueous binder sodium alginate (SA) and 0.7 g of negative electrode active material red phosphorus powder, and then add 2.1 mg of sodium sulfate and 1 g of water as raw materials. These raw materials are mechanically stirred for 60 min per cycle under a nitrogen atmosphere, with an interval time of 60 min, and the mechanical stirring cycle is repeated 8 times to obtain slurry A; Step 2: Add 0.2 g of conductive agent KB to slurry A, and then add 0.9 g of water as a wet grinding agent and continue mixing for 8 h to obtain slurry B. Slurry B is directly coated to obtain a uniformly coated electrode A; Step 3, the coated electrode A obtained in step 2 is dried in a 60°C oven for 8 h to obtain a negative electrode of the battery; Application Example 4 This application example relates to a negative electrode sheet for a sodium ion battery, wherein the negative electrode is Sn4P3 powder, and the preparation method thereof is as follows: Step 1, weighing 0.5 g of aqueous binder sodium carboxymethyl cellulose (CMC-Na) and 3.5 g of negative electrode active material Sn4P3 powder, and then adding 117.5 mg of sodium carbonate and 19.5 g of water as raw materials, these raw materials are ball-milled in an argon atmosphere for 30 min per cycle, with an interval time of 60 min, and mechanically stirred for 24 cycles to obtain slurry A; Step 2, add 1 g of conductive agent KB to slurry A, continue mixing for 4 h to obtain slurry B, and directly apply slurry B to obtain a uniformly coated electrode A; Step 3, the coated electrode A obtained in step 2 is dried in a 60°C oven for 8 h to obtain a negative electrode of the battery; Application Example 5 This application example relates to a negative electrode sheet for a sodium ion battery. The negative electrode is SbP powder, and the preparation method thereof is as follows: Step 1, weighing 0.2 g of aqueous binder sodium polyacrylate (PAA-Na) and 1.4 g of negative electrode active material SbP powder, and then adding 70 mg of anhydrous sodium fluoride and 11.8 g of water as raw materials, these raw materials were ball-milled in a nitrogen atmosphere for 60 min per cycle, with an interval time of 90 min, and the ball-milling cycle was repeated 10 times to obtain slurry A; Step 2, add 0.4 g of conductive agent MCNT to slurry A, continue mixing for 2 h to obtain slurry B, and directly apply slurry B to obtain a uniformly coated electrode A; Step 3, the coated electrode A obtained in step 2 is dried in a 60°C oven for 8 h to obtain a negative electrode of the battery; Comparative Example 1 The preparation process and coating ratio are consistent with those in Application Example 1, and the active substance adopts the raw material before wet grinding interface construction treatment.

[0051] Comparative Example 2 The preparation process and coating ratio of Application Example 2 are consistent with those of Application Example 2, and the active substance adopts the raw material before wet grinding interface construction treatment.

[0052] Comparative Example 3 The preparation process and coating ratio are consistent with those in Application Example 3, and the active substance adopts the raw material before wet grinding interface construction treatment.

[0053] Comparative Example 4 The preparation process and coating ratio are consistent with those in Application Example 4, and the active substance adopts the raw material before wet grinding interface construction treatment.

[0054] Comparative Example 5 The preparation process and coating ratio are consistent with those in Application Example 5, and the active substance adopts the raw material before wet grinding interface construction treatment.

[0055] The electrode sheets and sodium sheets obtained in the above application examples and comparative examples were assembled into half-cells in a glove box with water and oxygen values ​​less than 0.01 ppm, and the electrochemical performance tests were carried out on the Xinwei. The specific steps are: Example 1 and Comparative Example 1 were charged and discharged at a current density of 100 mA / g, and their charge and discharge curves were compared; Example 2 and Comparative Example 2 were cycled at a current density of 660 mA / g to compare their cycle performances; Example 3 and Comparative Example 3 were charged and discharged at a current density of 100 mA / g; and their charge and discharge curves were compared; Example 4 and Comparative Example 4 were cycled at a current density of 100 mA / g to compare their cycle performances; Example 5 and Comparative Example 5 were charged and discharged at a current density of 100 mA / g, and their charge and discharge curves were compared; The electrode sheets obtained in Example 1 and Comparative Example 1 were used to perform the first cycle of charge and discharge at a current density of 100 mA / g, and the first cycle of charge and discharge coulomb efficiency (first cycle coulomb efficiency = first cycle charge capacity / first cycle discharge capacity) was calculated. Figure 1 It can be seen that Application Example 1 has a higher charge-discharge capacity and a higher first efficiency, and thus has a higher reactivity. This is because wet grinding nano-sizes tin, which accelerates the transmission of sodium ions and the infiltration of electrolytes, thereby increasing the possibility of contact between the material and sodium ions, making it easier to deintercalate sodium.

[0056] The electrode sheets obtained in Example 2 and Comparative Example 2 were subjected to charge and discharge cycles at a current density of 660 mA / g ( Figure 2 ), calculate the capacity retention rate after different number of cycles (capacity retention rate = capacity after a specific number of cycles / capacity of the first cycle at the same current density). Figure 2 It can be seen that Application Example 2 has better cycle stability in 175 cycles, and the capacity has almost no attenuation. This is because the composite interface construction layer formed by adding sodium chloride acts as a "protective cover" for the material shell structure, inhibiting the decomposition of the electrolyte, and the interface construction layer effectively inhibits the volume expansion of Sb during the cycle, avoiding the crushing and pulverization of Sb, thereby improving the cycle performance. At the same time, nano-sizing can also alleviate the volume stress when antimony is deintercalated into sodium, further improving the cycle performance of antimony.

[0057] The electrode sheets obtained in Example 3 and Comparative Example 3 were charged and discharged for the first cycle at a current density of 100 mA / g, and the first cycle charge and discharge coulomb efficiency was calculated (first cycle coulomb efficiency = first cycle charge capacity / first cycle discharge capacity). Figure 3It can be seen that Application Example 3 has a higher charge-discharge capacity and a higher first efficiency, and thus has a higher reactivity. This is because wet grinding nano-sizes phosphorus, which accelerates the transmission of sodium ions and the infiltration of electrolytes, thereby increasing the possibility of contact between the material and sodium ions, making it easier to deintercalate sodium.

[0058] The pole pieces obtained in Example 4 and Comparative Example 4 were subjected to charge and discharge cycles at a current density of 1000 mA / g ( Figure 2 ), calculate the capacity retention rate after different number of cycles (capacity retention rate = capacity after a specific number of cycles / capacity of the first cycle at the same current density). Figure 4 It can be seen that Application Example 4 has better cycle stability, the capacity remains stable, and there is almost no attenuation. This is because the composite interface construction layer formed by adding sodium carbonate acts as a "protective cover" for the material shell structure, inhibiting the decomposition of the electrolyte, and the interface construction layer effectively inhibits the volume expansion of Sn4P3 during the cycle, avoiding the crushing and pulverization of Sn4P3, thereby improving the cycle performance. At the same time, nano-sizing can also alleviate the volume stress of Sn4P3 when deintercalating sodium, further improving the cycle performance of antimony.

[0059] The electrode sheets obtained in Example 5 and Comparative Example 5 were charged and discharged for the first cycle at a current density of 100 mA / g, and the first cycle charge and discharge coulomb efficiency was calculated (first cycle coulomb efficiency = first cycle charge capacity / first cycle discharge capacity). Figure 5 It can be seen that Application Example 5 has a higher charge-discharge capacity and a higher first efficiency, and thus has a higher reactivity. This is because wet grinding nanosizes SbP, which accelerates the transmission of sodium ions and the infiltration of electrolytes, thereby increasing the possibility of the material contacting sodium ions and making it easier to deintercalate sodium.

[0060] The above embodiments are only specific embodiments of the present invention, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and these obvious replacement forms all belong to the protection scope of the present invention.

Claims

1. A negative electrode sheet for a sodium ion battery, comprising a negative electrode current collector and a negative electrode material layer coated on the negative surface and / or positive surface of the negative electrode current collector, characterized in that: The negative electrode material layer comprises the following raw material components in parts by weight: 10 parts of aqueous binder, 70-80 parts of negative electrode material powder, 0.7-4 parts of inorganic salt interface constructor, and 10-20 parts of conductive agent; the raw material components in the negative electrode material layer are dispersed in a wet grinding solvent system and mixed uniformly by wet grinding under a protective atmosphere.

2. The negative electrode sheet for a sodium ion battery according to claim 1, characterized in that: The ratio of the raw material components to the wet grinding solvent is 1:1-1:

20.

3. The negative electrode sheet for a sodium ion battery according to claim 2, characterized in that: The inorganic salt interface constructor is one or more of NaF, NaCl, Na2SO4, NaNO3, and Na2CO3.

4. The negative electrode sheet for a sodium ion battery according to claim 3, characterized in that: During the wet grinding process, the process control conditions are: under a protective atmosphere, cyclic ball milling is carried out in an intermittent manner, the ball milling time for each cycle is 30-90 minutes, the interval time is 60-90 minutes, and the number of ball milling cycles is 4-24 times; the ball milling frequency is in the range of 40-50Hz, so that the particle size after ball milling reaches between 200-1000nm.

5. The negative electrode sheet for a sodium ion battery according to claim 4, characterized in that: The elements of the negative electrode powder are composed of one or more of the sodium-intercalating active elements silicon, lead, tin, antimony, germanium, bismuth, phosphorus, and sulfur, or a combination of one or more of the non-sodium-intercalating active elements zinc, iron, cobalt, nickel, copper, and aluminum and one or more of the above-mentioned sodium-intercalating active elements.

6. The negative electrode sheet for a sodium ion battery according to claim 5, characterized in that: The water-based binder is one or more of carboxymethyl cellulose, polyacrylic acid, sodium alginate, sodium carboxymethyl cellulose, and sodium polyacrylate.

7. The negative electrode sheet for a sodium ion battery according to claim 6, characterized in that: The conductive agent is one or more of carbon black, conductive graphite, carbon fiber, carbon nanotube, graphene, Ketjen black and acetylene black.

8. The negative electrode sheet for a sodium ion battery according to claim 7, characterized in that: The wet grinding method is one or more of ball milling, sand milling, homogenizer mixing, deaerator homogenization, or mechanical stirring.

9. The negative electrode sheet for a sodium ion battery according to claim 8, characterized in that: The protective atmosphere is argon or nitrogen.

10. The negative electrode sheet for a sodium ion battery according to claim 9, characterized in that: The wet grinding solvent system in the wet grinding process is water.

Citation Information

Patent Citations

  • Sodium-ion battery water-based negative electrode plate with high stability

    CN117747792A